Calculation the production cross-section of the BSM boson via photon fusion reaction - Barabash, O. V. (Київський національний університет імені Тараса Шевченка, 2019)
The production cross-section of the beyond the standard model (BSM) scalar boson (S-boson) have been considered it the article. Scalar boson produced via photon fusion reaction in the deep inelastic scattering of a charged particle (proton or electron) on heavy nucleus of the target. This process is one of the possible mecha- nisms of BSM boson production at the SHiP (Search for Hidden Particles) experiment at the CERN LHC and may be dominating among others processes due to large nuclear charge. In a low-energy case for which virtual photon wavelength similar or bigger nuclear size one can consider nucleus as an elementary particle with the charge Z. Corresponding amplitude is proportional to Z and the cross-section proportional to Z^2. Due to this the alpha_{EM}^2 suppression of the production cross-section is approximately compensated by the charge number factor Z^2. The mass of boson cannot exceed 4 MeV for the incident proton (or less than 80 MeV for electron). We calculated amplitude and the production cross-section of this reaction directly without using equivalent photon approximation. Interaction between photon and neutral boson is described by triangular diagrams with the loop containing all charged leptons, quarks and W-bosons. For this interaction we used effective lagrangian. The found cross-section was analyzed for the case of proton scattering on the lead nucleous and compared with the production cross-section in the decay of Ds mesons. It was found that the photon fusion reaction becomes effective only with a S-boson mass less than 0.1 keV.Key words: SHiP, production cross-section, BSM scalar boson, photon fusion reaction.Pages of the article in the issue: 94 - 97Language of the article: Ukrainian